Use of Information and Communication Technologies as an educational media in health: integrative review (Research, Society and Development, 2020)
Objective: To analyze in the scientific literature, the proposals on the use of Information and Communication Technologies, by health professionals for health education. Methodology: this is an integrative literature review, carried out in the first semester of 2019. The study is divided into six stages, namely: Identification of the theme; Definition of inclusion and exclusion criteria; Extraction of information; Analysis of studies; Discussion of results and presentation of the review. Articles published between 2008 and 2018 were included. Results: of a total of 826 articles, 15 articles were included that fit the scope of the research question. The most used technologies were the development of a virtual environment for Distance Education, construction and application of online courses for health education. Conclusion: There is a need to use new methods capable of bringing users closer to nurses, who must be trained and updated, to monitor technological development and socialize scientific and updated information.